Crash & burn [large type] - Gardner, Lisa (Thorndike Press, a part of Gale, Cengage Learning, 2015)
Nicole Frank, after surviving a car accident, enlists the help of Boston police officer Sergeant Wyatt Foster to find a missing girl. Who is Nicky Frank, and what happened the night her car sailed off the road? Was it a random accident or something more sinister given the woman's lack of family and no close friends? The deeper Wyatt digs, the more concerned he becomes. Because it turns out, in the past few months, Nicky has suffered from more than one close accident. In fact, it would appear someone very much wants her dead.